2018
DOI: 10.3389/fpubh.2018.00038
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Associated with Low Adherence to the Mediterranean Diet and Adverse Health Conditions in Portuguese Adults

Abstract: BackgroundFood insecurity is a limited or uncertain access to the adequate food and is a significant public health problem. We aimed to assess determinants of food insecurity and the corresponding health impact in Portugal, a southern European country that faced a severe economic crisis.MethodsData were derived from the Epidemiology of Chronic Diseases Cohort Study (EpiDoC), a population-based cohort of 10,661 individuals that were representative of the Portuguese adult population and followed since 2011. A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 31 publications
5
77
2
9
Order By: Relevance
“…The increasing availability of foods from big retail is a revolutionary event that has impacted health on a population-size level. In particular, the adherence to the Mediterranean diet is decreasing even within those regions where it was first discovered [11,12], and such a change in the alimentary habit is generally seen as one of the potential causes of the obesity epidemic [13], especially among adolescents [14].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability of foods from big retail is a revolutionary event that has impacted health on a population-size level. In particular, the adherence to the Mediterranean diet is decreasing even within those regions where it was first discovered [11,12], and such a change in the alimentary habit is generally seen as one of the potential causes of the obesity epidemic [13], especially among adolescents [14].…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, data obtained through the EpiDoc cohort (2015–2016) in a representative sample of the Portuguese population, showed that 19.3% of the portuguese population had some level of FI, and that 1.8% were classified as having severe FI ( 4 , 5 ). Among older adults, the prevalence of FI seems to be higher.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted in a cohort of the Portuguese population, food insecurity has a prevalence of 19.3%. Additionally, this study has shown that Portuguese food-insecure individuals have a higher risk of having unhealthy dietary patterns (lower adherence to the Mediterranean diet) and chronic diseases, resulting in higher healthcare resource consumption [ 24 ]. Data from the last National Health Survey showed a social gradient in the prevalence of chronic diseases such as diabetes, hypertension and obesity.…”
Section: Resultsmentioning
confidence: 99%